Analisis Sumber Air, Kepemilikan Septictank terhadap Total Coliform Air di Rumah Tangga Kecamatan Dumai Selatan Kota Dumai - Siirin, Shoffi Aufa; Nanda, Meutia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
A new study released by UNICEF in 2022, states that nearly 70 percent of the 20,000 household drinking water sources tested in Indonesia have been contaminated with fecal waste and one of the causes of the spread of diarrheal diseases. Based on data from the Bumi Ayu Health Center (2022), households are still found using the plengsengan and cemplung types of latrines. Improper fecal drainage conditions make clean water sources and drinking water cannot be used directly so that it can have an impact on public health. The purpose of this study was to analyze the source of water and septic tank ownership with total Coliform household clean water in the District of South Dumai. This study uses quantitative research with cross sectional design. Sampling technique is done by purposive sampling technique. The Data were obtained by using questionnaires and laboratory tests of clean water samples (Wells) consumed and <10 m with a septictank of 10 samples. The results of the questionnaire were analyzed using the chi square test and it is known that the entire sample contains total coliform bacteria (> 50 MPN). It is known that there is a relationship between the source of clean water used by respondents with septic tank ownership. Then the results of the analysis with total coliform content showed that all samples of well water, which is a subsurface water source, were contaminated by total coliform bacteria so that they did not meet hygiene and health standards. The suggestion is that people should be more selective in choosing and using water sources for consumption. Keywords: Septictank, Total Coliform, Water Source, Well Water